Testing the Waters : Aboriginal Title Claims to Water Spaces and Submerged Lands – An Overview - Quig, Paula (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 2004)
This article provides an overview of some of the intriguing issues raised by Aboriginal title claims to water spaces and submerged lands. While the Supreme Court of Canada articulated a test for proof of Aboriginal title in the 1997 Delgamuukw decision, they did not squarely address questions relating to the viability of such claims outside of the “dry land” context. Recently, a number of Aboriginal groups from across Canada have filed claims seeking declarations of Aboriginal title in areas such as the foreshore, the sea, the seabed, and the Great Lakes and their connecting waterways. Similar claims might also surface in Quebec in the near future, in areas such as the St. Lawrence Seaway. The author guides the reader through international developments in this area, highlights some key legal and evidentiary issues which will require serious reflection in the near future, and provides some final thoughts with respect to the fundamental role which the goal of reconciliation and the principle of consultation will undoubtedly play in Aboriginal title cases to water spaces and submerged lands.